2011
DOI: 10.1186/1476-4598-10-55
|View full text |Cite
|
Sign up to set email alerts
|

miR-34a and miR-15a/16 are co-regulated in non-small cell lung cancer and control cell cycle progression in a synergistic and Rb-dependent manner

Abstract: BackgroundmicroRNAs (miRNAs) are small non-coding RNAs that are frequently involved in carcinogenesis. Although many miRNAs form part of integrated networks, little information is available how they interact with each other to control cellular processes. miR-34a and miR-15a/16 are functionally related; they share common targets and control similar processes including G1-S cell cycle progression and apoptosis. The aim of this study was to investigate the combined action of miR-34a and miR-15a/16 in non-small ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(105 citation statements)
references
References 49 publications
(71 reference statements)
6
99
0
Order By: Relevance
“…In addition, the ectopic miR-15a-5p and miR-16, were able to inhibit growth and induce apoptosis in some tumors with high Bcl-2 expression levels. 6,[61][62][63] The present findings broaden the role of the miR-15a/16 cluster to activate apoptosis cascade in Bcl-x L -overexpressing tumors by miR-15a-3p. These findings extend the potential of this miRNA cluster as a tumor suppressor in cancer-related miRNAs therapies.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, the ectopic miR-15a-5p and miR-16, were able to inhibit growth and induce apoptosis in some tumors with high Bcl-2 expression levels. 6,[61][62][63] The present findings broaden the role of the miR-15a/16 cluster to activate apoptosis cascade in Bcl-x L -overexpressing tumors by miR-15a-3p. These findings extend the potential of this miRNA cluster as a tumor suppressor in cancer-related miRNAs therapies.…”
Section: Discussionsupporting
confidence: 56%
“…miR-34 family mediates such functions through additive or synergistic effects on multiple targets, including cyclin-dependent kinase 4 (CDK4), CDK6, E2F3, cyclin D1, cyclin E2, Bcl-2, and others (Antonini et al 2010;Bommer et al 2007;Sun et al 2008). Reportedly, miR-34a is able to down-regulate the antiapoptosis protein Bcl-2 in non-small cell lung cancer and induce apoptosis by activating apoptotic protein caspase-3 in pancreatic cancer stem cells (CSCs) (Bandi and Vassella 2011;Nalls et al 2011). Our data revealed that lanthanum chloride induced a significant increase of mir-34a and a decrease in Bcl-2 and Cyclin D1 levels, finally resulted in cell cycle arrest at G1 phase.…”
Section: Discussionmentioning
confidence: 99%
“…miR-155 and miR-21) (5). Indeed, several miRNAs are reported to have important roles in different types of cancer, including acute myelogenous leukemia (6,7), chronic myelogenous leukemia (CML) (8)(9)(10), lung cancer (11,12), and breast cancer (13), among others. miRNAs have also been shown to play a role in cancer progression through the modulation of cellular adhesion, cell matrix and signaling activities (14,15).…”
mentioning
confidence: 99%